2017
DOI: 10.1038/s41598-017-13417-w
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor in Cartilage Development and Osteoarthritis

Abstract: Genome wide studies indicate that vascular endothelial growth factor A (VEGF) is associated with osteoarthritis (OA), and increased VEGF expression correlates with increased disease severity. VEGF is also a chondrocyte survival factor during development and essential for bone formation, skeletal growth and postnatal homeostasis. This raises questions of how the important embryonic and postnatal functions of VEGF can be reconciled with an apparently destructive role in OA. Addressing these questions, we find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 44 publications
4
98
1
Order By: Relevance
“…Inflammatory and angiogenic molecules, such as TNF‐α and VEGF (Nagao et al, ), are well‐known catabolic meditators. They can stimulate matrix degrading enzymes (e.g., MMPs and ADAMTS), which in turn leads to acceleration of IVD degeneration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory and angiogenic molecules, such as TNF‐α and VEGF (Nagao et al, ), are well‐known catabolic meditators. They can stimulate matrix degrading enzymes (e.g., MMPs and ADAMTS), which in turn leads to acceleration of IVD degeneration.…”
Section: Resultsmentioning
confidence: 99%
“…VEGFR‐2 activation could mediate the effects of VEGF on endothelial cell proliferation, differentiation, survival, migration, and permeability, thus contributing to vasculature development and maintenance in embryonic, fetal, postnatal, and adult period (Ferrara et al, ; Maharaj & D'Amore, ; Takahashi & Shibuya, ), as well as being essential in some pathological process such as tumor angiogenesis, tissue repair and remodeling, and so forth. Furthermore, accumulating evidence suggests that VEGF can induce and accelerate the development of knee OA through activation of VEGFR‐2 (Hamilton et al, ; Nagao et al, ). In our DDD mouse model, it was noted that both WT and vegfr‐1 TK−/− mice show similar presentations of disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, injecting VEGFA into both keen and temporomandibular joint induced OA phenotype in mice . Correspondingly, another study reported that either deleting VEGFA in Col Π‐Cre lineage cells or intra‐articular injecting anti‐VEGFA antibody attenuated progression of surgically induced OA in mice . These findings suggest that controlling VEGFA secretion may help prevent OA escalation and OA‐associated joint deterioration.…”
mentioning
confidence: 87%
“…Hif‐2α gene (Epas1) expression is higher in OA cartilage than normal cartilage and it promotes cartilage degradation in part by modulating the expression of Col10a1 , Mmp13 , or Vegfa . Abnormal expression of these factors can in turn drive cartilage destruction or mediate catabolic processes in OA chondrocytes . HIF‐2α can also mediate cartilage destruction by controlling MMP3 and MMP13 levels via IL‐6 expression and by inducing FAS‐mediated chondrocyte apoptosis, as shown in mice subjected to the destabilization of the medial meniscus (DMM) surgical OA model and in mice with intra‐articular injection of AdEpas1, which can induce OA.…”
Section: Transcriptional Network Driving Articular Chondrocyte Hypermentioning
confidence: 99%